Factors associated with repeat breeding in Holstein Friesian cows at the Tani Wilis Village Cooperative Unit, Sendang District, Tulungagung Regency, Indonesia - Dimas Kunto Satrio; M’ Izi Kumala Lazuardi Sultoni; Tasya Apritalia Putri; Soeharsono Soeharsono; Dadik Rahardjo; Djoko Legowo; Gandul Atik Yuliani; Iwan Sahrial Hamid; Mohammad Anam Al-Arif; Sunaryo Hadi Warsito; Pudji Srianto; Sri Pantja Madyawati; Tita Damayanti Lestari; Wurlina Wurlina (Universitas Airlangga, 2025)
This study aimed to evaluate the association of factors such as nutrition, thermal humidity index (THI), age, and lactation period with the occurrence of repeat breeding of dairy cows. The sample consisted of Holstein Friesian cows aged 1-11 years, with lactation periods ranging from 1 to 7 months, currently in lactation, and experiencing repeat breeding (inseminated three or more times without conception, despite exhibiting normal estrous cycles and intervals). The results showed that feeding practices by farmers did not significantly differ (p >0.05) in relation to the incidence of repeat breeding. THI values recorded in several barns also showed no significant differences (p >0.05), with the cows experiencing light to moderate heat stress. Similarly, the frequency of artificial insemination and the estrous cycle intervals remained within the normal range. The highest incidence of repeat breeding was observed in cows aged 2.5 to 5.5 years, accounting for 78.13%, and during lactation periods of 1-3 months, accounting for 81.26%. It can be concluded that there were no significant differences in the provision of forage and leguminous feed between normal cows and those with repeat breeding, and the crude protein content of forage did not influence its occurrence. Additionally, there was no indirect relationship between THI and repeat breeding. However, the incidence of repeat breeding tended to increase in cows aged 3-4 years, and during the second and third lactation periods.